Heritability and Clinical Characteristics of Neuropsychological Profiles in Youth With and Without Elevated ADHD Symptoms. Issue 11 (September 2022) - Arnett, Anne B.; McGrath, Lauren M.; Flaherty, Brian P.; Pennington, Bruce F.; Willcutt, Erik G.
Objective: In the last decade, there has been an increase in research that aims to parse heterogeneity in attention deficit hyperactivity disorder (ADHD). The current study tests heritability of latent class neuropsychological subtypes. Method: Latent class analysis was used to derive subtypes in a sample of school-age twins ( N = 2, 564) enriched for elevated ADHD symptoms. Results: Five neuropsychological profiles replicated across twin 1 and twin 2 datasets. Latent class membership was heritable overall, but heritability varied by profile and was lower than heritability of ADHD status. Variability in neuropsychological performance across domains was the strongest predictor of elevated ADHD symptoms. Neuropsychological profiles showed distinct associations with age, psychiatric symptoms and reading ability. Conclusion: Neuropsychological profiles are associated with unique neurocognitive presentations, but are not strong candidate endophenotypes for ADHD diagnosis.